Why Historical Research Frameworks Matter for Sociological Methods and Decolonial Approaches? Empire and Nation Compared with Intra- and Inter-Imperiality - Korhonen, Juho (Sosiologia, 2025)
Sociology faces many obstacles in coming to terms with its so-called imperial entanglements. In this article, I address one of the dimensions of this problem. Much like archival sources present their own histories of making and organization that researchers should be aware of, so too do disciplinary research frameworks carry their own histories and historical metaprinciples of organization. I juxtapose two different ways of organizing and framing sociology's disciplinary focus historically. I call these the empire and nation framework and the intra- and inter-imperial framework. Through this juxtaposition, I argue for the importance of methodologically explicitly recognizing and justifying our choice of different historical research frameworks with which sociology can operate.